Reflections on Phishing for Phools – The Economics of Manipulation and Deception - Thomas Klikauer (tripleC: Communication, Capitalism & Critique)
Abstract: Nobel Prize winning economists Akerlof and Shiller’s phishing for phools explains the economics behind mass deception and manipulation in market economies. While “phishing” is commonly known as a form of internet fraught, their book ‘takes a new, broader meaning, i.e. getting people to do things that are in the interest of the phisherman, but not in the interest of the target. A phool is someone who, for whatever reason, is successfully phished. These are emotional phools (feelings override common sense) and information phools (people act on information that is intentionally crafted to mislead them). Divided into “unpaid bills and financial crash”, “phishing in many contexts”, and “general lessons”, the book uses rafts of examples from economics, the media, and advertising to substantiate their claim. While it avoids linking their findings to capitalism, the book contains a few helpful hints when seeking to avoid being “phished as a phool”. In the end, and despite the economic analysis of the two Nobel Prize winners, the more illuminating book on the subject remains Lindstrom’s “Buyology”.